Les bactéries des sources hydrothermales profondes a l’origine de nouvelles molécules bioactives ? - Jean Guezennec (VertigO)
In the course of the discovery of novel polysaccharides of biotechnological interest, it is now widely accepted that extremophilic microorganisms will provide a valuable resource not only for exploitation in novel biotechnological processes but also as models for investigating how biomolecules are stabilized when subjected to extreme conditions. Deep-sea hydrothermal vents offer a new source of a variety of  fascinating microorganisms well adapted to these extreme environments. Over the past 15 years, an increasing number of new genera and species of both hyperthermophilic and mesophilic bacteria have been isolated from these deep-sea hydrothermal vents. This new bacterial diversity include strains able to produce under laboratory conditions, novel molecules such as polymers including exopolysaccharides and poly beta hydroxyalkanoates and other bioactive molecules.